CD36‐triggered cell invasion and persistent tissue colonization by tumor microvesicles during metastasis. Issue 2 (12th September 2018) - Pfeiler, Susanne; Thakur, Manovriti; Grünauer, Petra; Megens, Remco T. A.; Joshi, Urjita; Coletti, Raffaele; Samara, Verena; Müller-Stoy, Geraldine; Ishikawa-Ankerhold, Hellen; Stark, Konstantin; Klingl, Andreas; Fröhlich, Thomas; et al.
ABSTRACT: Tumor microvesicles are a peculiar type of extracellular vesicles that circulate in the blood of patients with metastatic cancer. The itineraries and immune cell interactions of tumor microvesicles during the intravascular and extravascular stages of metastasis are largely unknown. We found that the lipid receptor CD36 is a major mediator of the engulfment of pancreatic tumor microvesicles by myeloid immune cells in vitro and critically samples circulating tumor microvesicles by resident liver macrophages in mice in vivo . Direct nanoscopic imaging of individual tumor microvesicles shows that the microvesicles rapidly decay during engulfment whereby their cargo is targeted concomitantly to the plasma membrane and the cytoplasm excluding lysosomal compartments. CD36 also promotes internalization of blood cell (nontumor) microvesicles, which involves endolysosomal pathways. A portion of tumor microvesicles circulating in the liver microcirculation traverses the vessel wall in a CD36‐dependent way. Extravasated microvesicles colonize distinct perivascular Ly6C − macrophages for at least 2 wk. Thus, the microvesicles are increasingly integrated into CD36‐induced premetastatic cell clusters and enhance development of liver metastasis. Hence, promotion of metastasis by pancreatic tumor microvesicles is associated with CD36‐regulated immune cell invasion and extravasation of microvesicles and persistent infiltration of specific tissue macrophages by microvesicle cargo.—Pfeiler, S., Thakur, M., Grünauer, P., Megens, R. T. A., Joshi, U., Coletti, R., Samara, V., Müller‐Stoy, G., Ishikawa‐Ankerhold, H., Stark, K., Klingl, A., Fröhlich, T., Arnold, G. J., Wörmann, S., Bruns, C. J., Algül, H., Weber, C., Massberg, S., Engelmann, B. CD36‐triggered cell invasion and persistent tissue colonization by tumor microvesicles during metastasis. FASEB J. 33, 1860–1872 (2019). www.fasebj.org